A new species of the genus Kuwanimyia Townsend (Diptera: Tachinidae) from Zhanjiang, China - Zhao, Zhe; Zhang, Chun-Tian; Chen, Xiao-Lin (Zootaxa, 2012)
A new tachinid species, Kuwanimyia zhanjiangensis sp. nov., is described and illustrated based on specimens collectedfrom Zhanjiang in southern China. A modified key is provided for the identification of this species within the genus Ku-wanimyia Townsend, 1916. Figures showing characteristics distinguishing K. zhanjiangensis sp. nov. from the closely re-lated species K. conspersa Townsend (in particular, features of the male terminalia and male abdominal sternum 5) are included.